Współczesne metody fizjoterapii w rehabilitacji zespołu mięśnia piszczelowego przedniego = Modern physiotherapy methods in tibialis anterior syndrome rehabilitation - Marta Bała; Angelika Krzepkowska (Kazimierz Wielki University, 2016)
Bała Marta, Krzepkowska Angelika. Współczesne metody fizjoterapii w rehabilitacji zespołu mięśnia piszczelowego przedniego = Modern physiotherapy methods in tibialis anterior syndrome rehabilitation. Journal of Education, Health and Sport. 2016;6(7):228-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/ Bała Marta, Krzepkowska Angelika. Współczesne metody fizjoterapii w rehabilitacji zespołu mięśnia piszczelowego przedniego = Modern physiotherapy methods in tibialis anterior syndrome rehabilitation. Journal of Education, Health and Sport. 2016;6(7):228-235. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57353   http://ojs.ukw.edu.pl/index.php/johs/article/view/3666               The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015).   755 Journal of Education, Health and Sport eISSN 2391-8306 7   © The Author (s) 2016;   This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland   Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium,   provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License   (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited.   This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial   use, distribution and reproduction in any medium, provided the work is properly cited.   The authors declare that there is no conflict of interests regarding the publication of this paper.   Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.           WSPÓŁCZESNE METODY FIZJOTERAPII W REHABILITACJI ZESPOŁU MIĘŚNIA PISZCZELOWEGO PRZEDNIEGO       MODERN PHYSIOTHERAPY METHODS IN TIBIALIS ANTERIOR SYNDROME REHABILITATION       Marta Bała, Angelika Krzepkowska       Wydział Nauk o Zdrowiu, Śląski Uniwersytet Medyczny w Katowicach,   Koło Naukowe  Neurorehabilitacji przy Zakładzie Rehabilitacji Leczniczej Katedry Fizjoterapii Śląskiego Uniwersytetu Medycznego w Katowicach                   Wstęp:               Bieganie stało się jedną z najpopularniejszych aktywności sportowych we współczesnym świecie. Pozwala zadbać o kondycję fizyczną na wysokim poziomie, będąc treningiem aerobowym, przy czym nie wymaga drogiego sprzętu w porównaniu do innych dyscyplin. Zainteresowanie bieganiem wzrasta, według statystyk z roku 2011 w imprezach biegowych brało udział 9922 osób, natomiast już w 2013 roku liczba osób wzrosła do 57632. [1]               Poza poprawą kondycji, bieganie ma również ogromny wpływ na układ krążenia i układ oddechowy. Wzmacnia także układ immunologiczny, kształtuje sylwetkę, rozwija charakter, poprawia samopoczucie, regeneruje naszą siłę psychiczną motywując do dalszej pracy. Niestety, zbyt intensywny wysiłek, nieprawidłowo prowadzony trening i niedostateczna regeneracja często prowadzą do powstania licznych mikrourazów. Bagatelizowanie tych negatywnych czynników, może doprowadzić do  problemów, które mogą przerodzić się w poważną kontuzję. Jedną z nich jest zespół mięśnia piszczelowego przedniego. Jest to zmiana przeciążeniowa o charakterze narastającym dotykająca biegaczy trenujących na nierównych podłożach oraz pagórkowatych i twardych terenach. [2][3]   Cel pracy:   - Czym jest zespół mięśnia piszczelowego przedniego?   - Przegląd metod fizjoterapeutycznych stosowanych  w terapii mięśnia piszczelowego przedniego proponowanych przez literaturę.   - Analiza profilaktyki zespołu mięśnia piszczelowego przedniego.   Podsumowanie   Zespół mięśnia piszczelowego przedniego w praktyce klinicznej występuje w granicach od 4 do 35%, jest to dość częsty przypadek, chociaż równie często pomijany bądź błędnie diagnozowany.   Być może wzrost zainteresowania bieganiem spowoduje wzrost ilości artykułów na ten temat, które pozwolą usystematyzować daną jednostkę chorobową. Niewątpliwie jest to temat ciekawy i bardzo ważny dla fizjoterapeutów, którzy będą musieli w swojej karierze zmierzyć się z tym przypadkiem.   W procesie rehabilitacji wskazane jest przeprowadzenie wnikliwego badania podmiotowego oraz diagnozy.  Aby efekty pracy były widoczne koniecznym jest dobór odpowiednich metod fizjoterapeutycznych, wczesne rozpoczęcie terapii oraz systematyczność, natomiast ze strony pacjenta wymagana jest cierpliwość oraz konsekwentna praca, ponieważ tylko tak można osiągnąć cel postawiony przed terapią i powrócić do uprawiania dyscyplin sportowych.           Słowa kluczowe: zespół mięśnia piszczelowego przedniego, bieganie, metody fizjoterapeutyczne.           Introduction:   Running is one of the most popular sports activity. It allows to keep fit at a high level. It is an aerobic workout, which not require expensive equipment compared to other disciplines. Interest in running increases. According to statistic from 2011 in running events attended 9922 participants while in 2013 there was 57632. [1]   In addition to improving health, running also has a huge impact on the cardiovascular system and respiratory system. It affects also the immune system, shaped figure, develops  personality, improves  mood and motivates to better work. Unfortunately too intensive effort, improperly training and insufficient regeneration provoke to trauma. Underestimate of  this negative factors can lead to problems that can escalate  into serious injury. This may be tibialis anterior syndrome. It is a disease with an increasing overload. It affects runners who run on uneven, inflexible and hilly areas. [2][3]   Objectives:   -          What is the tibialis anterior syndrome?   -          Overview of physiotherapy methods used to treat tibialis anterior syndrome proposed by the literature.   -          Analysis of prevention tibialis anterior syndrome.   Summary   Tibialis Anterior Syndrome in clinical practice occurs within the limits of from 4 to 35%, this is quite a common case, although equally often overlooked or wrongly diagnosed. Perhaps the increased interest in running around will lead to an increase in the amount of articles on the subject, which will systematize the disease unit. Undoubtedly it is interesting and very important for physical therapists, who will have to in his career to deal with this case. In the process of rehabilitation, it is advisable to carry out an in-depth study of the subject and the diagnosis.  To work to be visible it is necessary the choice of appropriate methods of physiotherapy, early therapy and regularity, and the patient required is patience and consistent work, because only so can achieve the goal placed before treatment and return to practicing sports.           Key words: tibialis anterior syndrome, running, physiotherapy methods.